Hsp 70 expression and function during gametogenesis - Dix, David J. (Cell Stress Society International, 1997)
The dramatic transformations in nuclear content and cellular organization that occur during gametogenesis require unique regulation and execution of the mitotic and meiotic cell cycle, apoptotic cell death, DNA recombination and repair, and cellular differentiation. These processes are accompained by the constitutive and developmentally regulated expression of a number of hsp70 genes encoding 70 kDa heat shock proteins (Hsp70), including several hsp70s whose expression is unique to male germ cells. Examining the expression and function of Hsp70s in germ cells has provided significant insights into mechanisms of hsp70 gene regulation and Hsp70 protein function, as well as the developmental processes of gametogenesis.